Hepatitis C virus re‐treatment in the era of direct‐acting antivirals: projections in the USA. Issue 7 (29th January 2018) - Chhatwal, J.; Chen, Q.; Ayer, T.; Bethea, E. D.; Kanwal, F.; Kowdley, K. V.; Wang, X.; Roberts, M. S.; Gordon, S. C.
Summary: Background: The introduction of oral direct‐acting antivirals (DAAs) has dramatically changed the landscape of HCV treatment. However, a small percentage of patients fail to achieve sustained virologic response (SVR). Understanding the number of people who fail on DAAs and require re‐treatment is important for budget impact and disease burden projections. Aim: To quantify the number of HCV patients who fail to achieve SVR on oral DAAs (NS5A vs. non‐NS5A) and require re‐treatment. Methods: We used a mathematical model to simulate clinical management of HCV in the USA, which included the implementation of HCV screening, treatment, and disease progression. We simulated different waves of DAA treatment and used real‐world data to extract SVR rates and market shares of available therapies. Results: Our model projected that the number of people living without viraemia (i.e. cured) would increase from 0.70 million in 2014 to 1.78 million by 2020. Between 2014 and 2020, 1.50 million people would receive treatment with DAAs, of whom 124 000 (8.3%) are projected to fail to achieve SVR. Among those treatment failures, 66 600 (53.7%) patients would fail treatment with NS5A inhibitors and 69 600 (56.1%) would have cirrhosis. During the same period, 34 200 people would progress to decompensated cirrhosis and 27 300 would develop hepatocellular carcinoma after failing to achieve SVR. Conclusions: Even in the era of highly effective DAAs, a significant number of patients will fail to achieve SVR and will require re‐treatment options. Timely and effective re‐treatment is essential to prevent the long‐term sequelae of HCV.